A review shows that ATG10 has been identified as a potential prognostic marker and therapeutic target for cancer patients based on real-world studies - Ke Shi; Di Ke; Feng Li; Rong-Shu Shi; Tao Liu; Dan Li; Qun-Xian Zhang (Frontiers in Oncology)
Autophagy-related genes (ATGs) play a crucial role in tumorigenesis and cancer progression. ATG10, a member of the ATG family, has been implicated in various malignancies, including endometrial cancer, hepatocellular carcinoma, acute leukemia, nasopharyngeal carcinoma, gastric cancer and colorectal cancer. Its overexpression is frequently associated with poor prognosis and increased disease progression. ATG10 promotes cancer growth and metastasis by modulating epithelial-mesenchymal transition and cell cycle regulators such as cyclin B1, CDK1 and CDK2. However, its activity can be inhibited by several factors, including DDX10, PTBP1, sodium orthovanadate, podofilox, SIRT6, FAT1, SOX2 and multiple microRNAs (e.g., miR-369-3p, miR-100-3p, miR-27b-3p, miR-197-3p, let-7i-5p and miR-552). This review explores the functional and clinical significance of ATG10 across various cancers, highlighting its potential as a biomarker and therapeutic target.